Understanding the effectiveness of co-operative board members from resource dependence and participation perspective: a proposal of conceptual framework - Buang, Mokhtaruddin; Abu Samah, Asnarulkhadi (Human Resource Management Academic Research Society, 2021)
Co-operatives played a critical part in the community development initiative, and its viability is reliant on the board members' ability to carry out their roles effectively. Since board members are a vital body of the cooperative's internal governance, it is important to examine how they affect the cooperative's performance. Several factors have been proposed and based on prior research inferences, the majority of which have used the concept of corporate governance to identify the factors that influence the cooperative board's effectiveness, which has also been adopted in this article. Owing to the inconsistent findings and gaps in previous research, this article has focused on the role of board members' human and social capital in affecting cooperative performance. The research also presented board participation as a mediator between human and social capital and cooperative performance. This study employs resource dependence and participation theory as underpinning theories to support its assumptions and performs a literature review to synthesize empirical findings on related factors. SmartPLS software will be used to analyze the data and explore all relationships using Structural Equation Modeling (SEM).